The integration in the teaching of the subject «Self-cognition» (Journal of Educational Sciences, 2016)
The article describes the progress of the development of modern knowledge and modern science which is the One of the key priorities of Kazakhstan’s strategy for joining the ranks of the most developed and competitive countries in the world. Vector for the development of education aimed atensuring the quality of life that delimit by spirit concept as the main condition for the man and humanity’s full-fledged existence. And it detailed that the teacher’s today’s main purposes for solving this problem which are use a kind of spiritual and moral values to teach for the student, coverage thetreasures of the spiritual heart of learners and to improve each student as an individual along with the development of values. In this regard, this article also indicated the educational uncover method of subject integration which is one of the most important issues of teaching «Self – knowledge»subject in educational institutions. In order to meet the needs of society, S.A.Nazarbayeva who is the “Self – knowledge” spiritual and moral education project’s author and the First Lady of Kazakhstan raised the issue of the education for the younger generation on the basis of universal human values atthe state level for the first time. To talk about the priority of the spiritual and moral education must be well-considered the modern world’s global issues,the nature of the world of humanity, the integrity and moral valaues. And the total value of the human values to be opened. In this regard, this articleincludes a number of following issues of introduction the «Self – knowledge»subject for the practice of educational institutions. And the importance of spiritual and moral education institutions, organizations for the subject introduction of universal primary education, and integrate this subject with social sciences and natural Sciences subjects, and the possibility of its practice.
Keywords: discipline “self-cognition”; teaching “Self-cognition”; human values